Numerical Procedure for Long Term Deflection Prediction of Reinforced Concrete Elements Subjected to Different Load Histories - Docevska Marija; Markovski Goran; Arangjelovski Toni; Nakov Darko; Mark Peter (Macedonian Association of Structural Engineers, Faculty of Civil Engineering Skopje, 2017)
The influence of expected but idealized load histories typical for structural service conditions during life-time was studied with a special emphasis on long-term serviceability of RC structures. For that purpose, a numerical step-by-step cross-sectional procedure based on the Age-Adjusted Effective Modulus Method (AAEMM) has been developed and successfully verified through existing experimental results applying it on simply supported RC beams and one-way slabs. First results confirmed that individual load histories and precisely tracking the stiffness reduction with time, are significant to realistically reflect the long-term behaviour of RC elements.
Keywords: step-by-step, load history, long-term deflections, moment-curvature relations